The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1371/journal.pone.0205073
|View full text |Cite
|
Sign up to set email alerts
|

Differential profile of protein expression on human keratocytes treated with autologous serum and plasma rich in growth factors (PRGF)

Abstract: PurposeThe main objective of this study is to compare the protein expression of human keratocytes treated with Plasma rich in growth factors (PRGF) or autologous serum (AS) and previously induced to myofibroblast by TGF-β1 treatment.MethodsBlood from healthy donor was collected and processed to obtain AS and PRGF eye drops. Blood derivates were aliquoted and stored at -80°C until use. Keratocyte cells were pretreated for 60 minutes with 2.5 ng/ml TGF-β1. After that, cells were treated with PRGF, AS or with TGF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 45 publications
(42 reference statements)
2
8
0
1
Order By: Relevance
“…Finally, a recent study showed that PRGF eye drops were able to produce a significant reduction in the number of transforming growth factor (TGF)-β1-induced myofibroblasts in comparison to AS, suggesting that PRGF may promote corneal wound healing regeneration, reducing scar formation [15]. To understand the pathways by which PRGF exerts its antifibrotic potential in comparison to AS, a proteomic study was performed in HK cells differentiated to myofibroblasts, which previously were to be treated with PRGF or AS [23]. This study shows that PRGF treatment inactivated or reduced the activation of several proteins involved in the pathways, whereby TGF-β1 exerts its action to induce the formation of α-actin fibers on human corneal stromal keratocytes (HK), inducing their transformation to myofibroblasts.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, a recent study showed that PRGF eye drops were able to produce a significant reduction in the number of transforming growth factor (TGF)-β1-induced myofibroblasts in comparison to AS, suggesting that PRGF may promote corneal wound healing regeneration, reducing scar formation [15]. To understand the pathways by which PRGF exerts its antifibrotic potential in comparison to AS, a proteomic study was performed in HK cells differentiated to myofibroblasts, which previously were to be treated with PRGF or AS [23]. This study shows that PRGF treatment inactivated or reduced the activation of several proteins involved in the pathways, whereby TGF-β1 exerts its action to induce the formation of α-actin fibers on human corneal stromal keratocytes (HK), inducing their transformation to myofibroblasts.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the different PRGF-based formulations including injectable liquid, eye drops, clot and membrane (for outpatient treatment and surgical use) exert regenerative, anti-inflammatory, antifibrotic, anti-bacterial, proliferative and cell migration properties. [14][15][16] Therefore, CC therapy should be focused on regeneration and on avoiding inflammation and fibrosis before reaching the risk of corneal blindness or other ocular surface complications. In this particular study, and intending to avoid the potential risk of certain side effects related to the PRGF's IgE levels and complement activity in autoimmune diseases or other refractory cases to the treatment, we decided to apply Immunosafe PRGF formulations.…”
Section: Discussionmentioning
confidence: 99%
“…The protocol for the preparation of Endoret-PRGF eye drops (ePRGF) is described in the kit's instructions for use, and it has been published by Anitua and Col. 15,16,20 The procedure was carried out under sterile conditions in the surgical room. To prepare the ePRGF, 70 mL of peripheral blood was collected into 9 mL tubes with 3.8% sodium citrate as an anticoagulant.…”
Section: Preparation and Use Of Immunosafe Prgfmentioning
confidence: 99%
See 1 more Smart Citation
“…El PRP es un hemoderivado con alta concentración de plaquetas, que puede servir para regeneración celular y activación biológica de diversos sistemas para responder a procesos traumáticos, degenerativos o infecciosos. Los factores de coagulación y citocinas están almacenados principalmente dentro de los gránulos alfa (Castro-Piedra & Arias-Varela, 2019), que son los responsables de inducir diferentes respuestas biológicas en la hemostasias y regeneración, constituyendo también el plasma rico en factores de crecimiento (PRFC) (Alcazar-Rubio et al, 2015;Anitua et al, 2018) (Tabla 1). La capacidad de cicatrización, regeneración y defensa está modulada por las células mesenquimales como células madre que dan origen a la mayoría de las células (Hersant et al, 2019).…”
Section: Composición De Prpunclassified